Quantitation of apolipoprotein ε gene expression by competitive polymerase chain reaction in a patient with familial apolipoprotein E deficiency - Dobmeyer, Jürgen; Rexin, Martin; Dobmeyer, Thomas S; Klein, Stefan A; Rossol, Rita; Feussner, Giso (Clinica chimica acta, 1998)
A simple method of obtaining semiquantitative and reliable data on apolipoprotein (apo) ε gene expression is described. We detected apo ε specific sequences by reverse transcription (rT)-PCR. For quantitative measurement, an apo ε DNA standard was produced allowing the development of a competitive PCR-method. The efficiency of RNA extraction and cDNA synthesis was controlled by quantitation of a housekeeping gene (glyceraldehyde-3-phosphatedehydrogenase, G3PDH) in separate reactions. To imitate a defined induction of apo ε gene expression, serial twofold dilutions of total RNA were reversely transcribed and the respective cDNAs used to perform a competitive apo ε and G3PDH PCR. The change in apo ε cDNA and G3PDH cDNA was 1.7-2.3-fold with an expected value of 2.0-fold. Standard deviations in three independently performed experiments were within a range of <15% of the mean, indicating low intra-assay variation and high reproducibility. To illustrate this method, apo ε gene expression was measured in a patient with complete lack of functional active apo E in comparison to healthy controls. The method presented here might be valuable in assessment of apo ε gene expression in human disease.
Gesehen am 30.01.2025